Konseptualisasi Peserta Didik dalam Kerangka Falsafah Tarbiyah Islamiyah - Muhammad Zaky Dhiyaul Haq; Syahidin (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2025)
This article discusses the concept of learners in the perspective of Islamic education philosophy, which emphasizes the importance of the role of learners as subjects of learning with physical and spiritual potential that must be developed holistically. In Islamic education, learners are seen as beings who are in a process towards perfection through learning spiritual, moral, and intellectual values. Education does not only aim to hone academic skills, but also to shape noble character based on Islamic values.Learners are identified through terms such as mutarabbi, muta'allim and muta'addib, which describe the dimensions of nurturing, learning and moral formation. In addition, the article highlights the importance of learner ethics involving respect for educators, sincere intentions, and earnestness in the pursuit of knowledge.With a holistic approach to education, learners are not just passive recipients of knowledge, but active individuals who are responsible for actualizing knowledge in their daily lives. Islamic education emphasizes the formation of a complete human being who is intellectually intelligent, spiritually rich, and has a noble character, with the ultimate goal of getting closer to Allah. This article also concludes that education in Islam is a continuous spiritual and intellectual transformation, placing learners as an integral part in the effort to continue the mission. Artikel ini membahas konsep peserta didik dalam perspektif filsafat pendidikan Islam, yang menekankan pentingnya peran peserta didik sebagai subjek pembelajaran dengan potensi jasmani dan ruhani yang harus dikembangkan secara holistik. Dalam pendidikan Islam, peserta didik dipandang sebagai makhluk yang berada dalam proses menuju kesempurnaan melalui pembelajaran nilai-nilai spiritual, moral, dan intelektual. Pendidikan tidak hanya bertujuan untuk mengasah kemampuan akademis, tetapi juga membentuk karakter yang mulia berdasarkan nilai-nilai Islam.Peserta didik diidentifikasi melalui istilah seperti mutarabbi, muta’allim, dan muta’addib, yang menggambarkan dimensi asuh, belajar, dan pembentukan akhlak. Selain itu, artikel ini menyoroti pentingnya etika peserta didik yang melibatkan penghormatan kepada pendidik, niat yang tulus, dan kesungguhan dalam menuntut ilmu.Dengan pendekatan pendidikan yang menyeluruh, peserta didik tidak hanya menjadi penerima pengetahuan pasif, melainkan individu aktif yang bertanggung jawab untuk mengaktualisasikan ilmu dalam kehidupan sehari-hari. Pendidikan Islam memberikan penekanan pada pembentukan manusia paripurna yang cerdas secara intelektual, kaya secara spiritual, dan berakhlak mulia, dengan tujuan akhir mendekatkan diri kepada Allah. Artikel ini juga menyimpulkan bahwa pendidikan dalam Islam adalah transformasi spiritual dan intelektual yang berkelanjutan, menempatkan peserta didik sebagai bagian integral dalam upaya melanjutkan misi kekhalifahan di muka bumi.